Komunikasi Politik Akun Instagram @raffinagita1717 dalam Branding Personal Prabowo-Gibran di Pemilu 2024 - Adinda Rizky Amalia; Aina Fitralisti; Debi Pratama Putri; Resti Yulianti; Ade Rahmah (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study aims to analyze the impact of political communication conducted through the Instagram account @raffinagita1717 on the personal branding of the Prabowo-Gibran pair in the 2024 elections. The research employs a quantitative approach with a descriptive correlational design, involving 400 respondents who are followers of the account. Data collection techniques include questionnaires using a Likert scale, observation, and documentation. The collected data were analyzed using validity and reliability tests, linear regression, and Pearson correlation. The results indicate that political communication through the Instagram account @raffinagita1717 significantly influences the personal branding of the Prabowo-Gibran pair. A regression coefficient of 1.585 suggests that improved political communication directly contributes to strengthening their personal branding. Effective communication strategies, such as creative content, the involvement of influencers like Raffi Ahmad, and leveraging social media platforms with broad audiences, have helped build a positive public perception of this pair. This study highlights the importance of social media as an effective modern political communication channel, especially for reaching young voters. It is expected that the findings of this study can serve as a reference for developing more efficient digital-based political campaign strategies.